2021
DOI: 10.3390/su13084257
|View full text |Cite
|
Sign up to set email alerts
|

How Can Cultural Values and Entrepreneurship Lead to the Consideration of Innovation-Oriented or Non-Innovation-Oriented Countries?

Abstract: This study provides an analysis of the existing relationship between culture, entrepreneurship, and orientation towards innovation at the national level. Drawing on the creation of an Artificial Neural Network, and using a sample of 37 countries, this paper aims to catalogue each country as innovation-oriented or non-innovation-oriented considering the six cultural dimensions proposed by Hofstede’s model and the country´s entrepreneurial activity. The results achieved suggest that three of the cultural dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Shane (1992) argued that individualist cultures encourage innovation and invention, while collectivist cultures discourage innovation and invention. Individualistic societies are more innovative as their reward systems rely on personal achievements rather than ascription (Gorodnichenko and Roland, 2017; López-Cabarcos et al ., 2021).…”
Section: Literature Review: Culture and Innovationmentioning
confidence: 99%
“…Shane (1992) argued that individualist cultures encourage innovation and invention, while collectivist cultures discourage innovation and invention. Individualistic societies are more innovative as their reward systems rely on personal achievements rather than ascription (Gorodnichenko and Roland, 2017; López-Cabarcos et al ., 2021).…”
Section: Literature Review: Culture and Innovationmentioning
confidence: 99%
“…geographical bias, origins of the concept, sample selection (Dorfman and Howell, 1988; Moulettes, 2007; Hernik and Antonio Minguez, 2020). Despite the critics, the concepts of Hofstede’s research are still widely used (Rubio-Banón and Esteban-Lloret, 2016; Lewellyn and Muller-Kahle, 2020; Lee et al , 2021; López-Cabarcos et al , 2021). Most quantitative measures on culture still refer to at least one dimension that is conceptually similar to those of Hofstede’s (Gerlach and Eriksson, 2021) as replications of the study have also revealed (Taras et al , 2012) that in majority of cases they closely matched the country variation originally observed by Hofstede.…”
Section: Women’s Position In the Central And East European Countries ...mentioning
confidence: 99%
“…On the other hand, these aspects between national culture and innovation have had different approaches, among which are tourism (Ruiz-Ortega et al, 2021;Muskat et al, 2021), entrepreneurship (Chan et al, 2020;L opez-Cabarcos et al, 2021b), banking (Asaah et al, 2020), innovation (Lin et al, 2020;Kaufmann et al, 2021;Cake et al, 2020;L opez-Cabarcos et al, 2021a), Creation trajectories innovation international business (He et al, 2020;Rai et al, 2020;Gallego-Álvarez and Pucheta-Martínez, 2021;Xia and Liu, 2021;Baah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%